1998
DOI: 10.1038/bjc.1998.277
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antiemetic efficacy of granisetron and ondansetron in Oriental patients: a randomized crossover study

Abstract: Summary A double-blind randomized crossover trial was performed to compare the antiemetic efficacy of two 5-HT3 receptor antagonists, granisetron and ondansetron, in Chinese patients receiving adjuvant chemotherapy (cyclophosphamide, methotrexate and 5-fluorouracil) for breast cancer. Twenty patients were randomized to receive chemotherapy with either granisetron on day 1 and ondansetron on day 8 of the first cycle followed by the reverse order in the second cycle, or vice versa. The number of vomiting episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…However, the number of studies and eligible patients are heterogeneous within the different scenarios. Therefore, more studies may be necessary to firmly establish this issue, especially regarding the DHV and DHN settings that were ad- 15 Ͻ 25 patients per arm Kalaycio et al 16 Ͻ 25 patients per arm and bone marrow transplant patients Pellier et al 17 Not enough information to exclude for complete control of emesis in the first 24 hours or after 24 hours of chemotherapy administration Poon and Chow 18 Ͻ 25 patients per arm Perez et al 13 No data regarding antiemetics for the first cycle before the crossover to the other antiemetic Zeidman et al 19 Although the study included 60 patients, it included both highly and moderately emetogenic regimens having Ͻ 25 patients for each of these groups Because both arms of granisetron and of ondansetron had equivalent antiemetic efficacy in these three studies they were combined for the meta-analysis calculations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of studies and eligible patients are heterogeneous within the different scenarios. Therefore, more studies may be necessary to firmly establish this issue, especially regarding the DHV and DHN settings that were ad- 15 Ͻ 25 patients per arm Kalaycio et al 16 Ͻ 25 patients per arm and bone marrow transplant patients Pellier et al 17 Not enough information to exclude for complete control of emesis in the first 24 hours or after 24 hours of chemotherapy administration Poon and Chow 18 Ͻ 25 patients per arm Perez et al 13 No data regarding antiemetics for the first cycle before the crossover to the other antiemetic Zeidman et al 19 Although the study included 60 patients, it included both highly and moderately emetogenic regimens having Ͻ 25 patients for each of these groups Because both arms of granisetron and of ondansetron had equivalent antiemetic efficacy in these three studies they were combined for the meta-analysis calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Two different studies conducted by Poon et al in 1998 andLuis et al, 2006, observed the response to nausea and vomiting had achieved 70% in the patient who had received granisetron and the value was statistically significant 21,15 . Our observational findings are also consistent with their study.…”
Section: Discussionmentioning
confidence: 94%
“…More effective antiemetic protection should be considered for Chinese patients receiving chemotherapy, including the use of 5‐HT 3 receptor antagonists. In a study of Chinese patients receiving CMF for breast cancer, Poon and Chow (1998) showed that granisetron (at day 1) and ondansetron (at day 8), or the reverse, were equally effective in controlling nausea and vomiting. Acute vomiting was completely prevented in 67.5–72.5%, and acute nausea was completely prevented in 35–37.5%, depending on the order of the antiemetics (Poon & Chow 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Chinese patients receiving CMF for breast cancer, Poon and Chow (1998) showed that granisetron (at day 1) and ondansetron (at day 8), or the reverse, were equally effective in controlling nausea and vomiting. Acute vomiting was completely prevented in 67.5–72.5%, and acute nausea was completely prevented in 35–37.5%, depending on the order of the antiemetics (Poon & Chow 1998). Delayed emesis was, however, less satisfactorily controlled (complete control in 52.5% of patients).…”
Section: Discussionmentioning
confidence: 99%